Sosialisasi Pemanfaatan Kecerdasan Buatan Dalam Meningkatkan Pemahaman Teknologi Di Era Digital Untuk Gen Alpha - Erdi Sutriyatna; Eko Sutono (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Technological developments become increasingly numerous and diverse in today's digital era, and the rise in internet users, particularly among children and teenagers, is closely linked to the use of one such technology known as Artificial Intelligence (AI). Young children, often referred to as Generation Alpha, are growing up alongside smart technology and Artificial Intelligence (AI) in an environment where digital devices and the internet are an integral part of daily life. They may have encountered and used AI-powered applications or games without fully understanding the mechanisms behind them, and they interact with the virtual world almost constantly. The method of implementing the Community Service Activity (PkM) was a socialization program about AI technology conducted at the Villa Permata Serpong Housing Complex. This aimed to provide basic knowledge about AI so that children could understand the use of AI technology, whether for interaction, communication, or information sharing, and to broaden their understanding of the potential of AI as a tool to support learning, providing personalized and interactive learning experiences. The results of this PkM indicate that the socialization activities for Generation Alpha children were effective in improving digital literacy in understanding the basic concepts of AI, recognizing the functions and presence of AI in daily life for independent and responsible learning, and fostering awareness of the safe and positive potential of AI.